Development in Danish international air traffic - Christensen, Linda; Dargay, Joyce (Proceedings from the Annual Transport Conference at Aalborg University, 2013)
The paper is describing the development in international air traffic made by Danes and for all travellers out of Denmark in the period 2002 - 2012. Development in passengers, destination countries and prices is illustrated. The person kilometres by Danes have increased 80% or 7.2% per year in mean during the 10 years. This increase has been analysed by a panel data model. The conclusion found by modelling is the increasing travel activity first of all is driven by increasing income and to less extent by decreasing prices. The paper is furthermore showing how the international air traffic has got more effective and to what extent Low Cost Carriers have taken over an important part of the travel market.